Aircraft spacing for continuous descent approach in a terminal area based on required time of arrival at a metering fix. - Daniel Pisani Dias (2010)
Guiding arriving flights through congested terminal airspace has always been a challenge. As traffic builds up, controllers must often move traffic away from the airport until they can bring those flights in for landing, causing inefficiencies. A widespread implementation of Continuous Descent Approach (CDA) would result in significant reductions in environmental impact and airline operating costs, however, a significant barrier to system wide CDA implementation is the difficulty to merge and space flights so that the CDA is flown safely. The en route metering essentially allows flights to absorb any necessary arrival delays en route, with transition to the terminal area in a pre-planned sequence. When delays would be imposed, the priority of landing would be based on the calculated time of arrival for each flight at the last metering fix, using a First-Come-First-Served policy. The spacing between successive arriving flights needs to be sufficient to allow for other flights downstream to merge into the overall flow while maintaining the minimum required separation according to the applicable rules. This work describes the fundamental design of a decision-support tool and procedures for CDA in the Sao Paulo Terminal Radar Approach Control (SP-TRACON) with flight spacing based on Required Time of Arrival (RTA) at a metering fix. A linear programming model was used to establish required time of arrival at TRACON entry points to provide adequate separation on final approach following the Standard Terminal Arrival Routes (STARs). For this purpose, typical actual traffic data approaching to airports in the SP-TRACON were used to apply the sequence model and evaluate the potential benefits on throughput and delays for Sao Paulo - Guarulhos airport. Using the ATFM methodology developed in this work, the general delays applied to the traffics of the two selected days were 53.5% and 55.1% lower than the delays observed with ATFM measures used by air traffic controllers. For the peak hours considered, the methodology provided 25.5% and 30.1% delay reduction. The air traffic controllers role in the process and workload reduction is also discussed.